Effect Of Strategic Plan Implementation On Organizational Performance Of Energy Companies In Somalia - ELMI, HASSAN MOHAMUD; GICHINGA, DR. LUCY GICHINGA (IJRDO - Journal of Applied Management Science, 2018)
The main purpose of this study is to investigate the effect of strategic plan implementation on organizational performance: a case study of Banaadir Electric Company (BECO).The specific objectives are to analyze the effects of strategic leadership, structures, strategic resource allocation and strategic policies on organizational performance and to measure the combined contribution of four factors (strategic leadership, structure, strategic policies and strategic resources allocation) on organizational performance. A descriptive research design will be adopted for this study. The dependent variable of the study is organizational performance while the independent variables of the study were Leadership, structure, policies factors and resource allocation effect of organizational performance. Most companies struggle with implementation of strategic plans and therefore fail in performance enhancement and it appears that BECO has had serious problem in implementing the strategic plan and it is not yet understood how the key components of strategic implementation including leadership, functional policies, organization structure and resources allocation are responsible the performance of the company. This study Sought to establish the effect of strategic plan implementation on organizational performance in electric companies by answering the following research question; how strategic plan implementation affects the electric companies in Mogadishu? The population consists of the Banaadir Electric Company (BECO) Employees: and target populations were the Top Managers, Middle Managers and first line Managers. 79 of the Banaadir Electric Company (BECO) managers were used as the sample size representing the total population. Proportionate stratified random sampling technique will be used for this study. The primary data collection tool was used administered questionnaires. A pilot test was conducted with a few respondents before the questionnaire will be reviewed and then was distributed to the selected sample. The data collected in this study was analyzed using descriptive statistics through SPSS version 22 for windows to provide simple summaries in form of tables, figures and explore relationships between responses to different questions. The results reveal that strategic Leadership, structure, strategic policies and strategic resource allocation have significant and positive effects on organizational performance of energy companies in Mogadishu-Somalia. The study recommended that managers of energy companies in Mogadishu -Somalia should nurture and develop strategic Leadership, structure, strategic policies and strategic resource allocation. The areas for further research include a comparative study between a public enterprise and a private enterprise to find out best practices that can be incorporated in the other sector.